Фрактальна графіка графічного дизайну - Лобода, Д. А. (ХНУРЕ, 2023)
Among all the images that a computer can create, few can compete with fractal images when it comes to true beauty. For most of us, the word "fractal" brings to mind colored curls that form a complex, thin and complex pattern. But in fact, this term has a much broader meaning. In the article, fractal graphics are stagnant in graphic design, as a sign of variability and visual building. One can see examples of fractals in the design of logos, packaging, posters, and advertising banners. We also look at the practical aspects of working with fractal images in graphic design programs. And we will also learn about the irreplaceability of frontal graphics in various areas of our lives and our future.
Keywords: графічний дизайн; фрактальна графіка